The social perception of monastic life between falsity and reality in contemporary world - Nina Stănescu, (Technium Social Sciences Journal, 2020)
Analysis of the misled mundane perceptions of monasteries and monastic life, and finding ways to change this concepts to the appropriate social reality in order to improve relations between the mundane and the monastic population, and also to increase the role of monasteries in moral and spiritual development of adolescents and youth. The key to this problem is communion, meaning together-living, together-working and together-thinking. The great revelation of Christianity was and is that the community comes first, either the big or the small communtiy. Great empires have induced the illusion that the great things, the secrets and the keys to our lives they are somewhere above or outside the small circle of our lives.